Fetal death and preterm birth associated with maternal influenza vaccination: systematic review. (10th July 2014) - Fell, DB; Platt, RW; Lanes, A; Wilson, K; Kaufman, JS; Basso, O; Buckeridge, D
<x xml:space="preserve">Abstract</x> Background Before 2012, few studies had addressed pregnancy outcomes following maternal influenza vaccination; however, the number of publications on this topic has increased recently. Objectives To review comparative studies evaluating fetal death or preterm birth associated with influenza vaccination during pregnancy. Search strategy We searched bibliographic databases from inception to April 2014. Selection criteria Experimental or observational studies assessing the relationship between influenza vaccination during pregnancy and fetal death or preterm birth. Data collection and analysis Two reviewers independently abstracted data from studies meeting the inclusion criteria. Main results We included one randomised clinical trial and 26 observational studies. Meta‐analyses were not considered appropriate because of high clinical and statistical heterogeneity. Three studies of fetal death at any gestational age reported adjusted effect estimates in the range 0.56–0.79, and four of five studies of fetal death at <20 weeks reported adjusted estimates between 0.89 and 1.23, all with confidence intervals including 1.0. Adjusted effect estimates for four of five studies of fetal death at ≥20 weeks ranged from 0.44 to 0.77 (two with confidence intervals not crossing 1.0), whereas a fifth reported a non‐significant effect in the opposite direction. Among 19 studies of preterm birth, there was no strong evidence suggesting any increased risk, and meta‐regression did not explain the moderate between‐study heterogeneity (I2 = 57%). Authors' conclusions Most studies reported no association between fetal death or preterm birth and influenza vaccination during pregnancy. Although several reported risk reductions, results may be biased by methodological shortcomings of observational studies of influenza vaccine effectiveness.